Autophagic-Related Anticancer Effect of Grapes Extract and Tomatoes Extract: Ex-Vivo Study - Elshafei, Marwa M.; Helmy, Iman M.; Sayed, Marwa M.; Farag, Doaa B.; Shebl, Ismail M.; Ghazy, Shaimaa E.; Afifi, Nermeen S. (Odovtos - International Journal of Dental Sciences, 2023)
Cells undergo autophagy to save themselves from injury, but progressive autophagy can cause cell death. This study characterized and compared the effect of grape (resveratrol) and tomato (lycopene) extracts and their combination on modulating autophagy-related miRNA and its target gene in squamous cell carcinoma cell line. Docking analysis for extracts and selected genes was performed. Methyl Thiazol Tetrazolium assays were used to assess the cytotoxicity of extracts and their combination toward HEp-2 cells. qRT-PCR was used to quantify changes in gene expression. Data were statistically analyzed. miRNA-20a was identified as a potential effector in laryngeal cancer, and sequestosome-1 (SQSTM1) was its target gene. Docking analysis showed that resveratrol interacted with miRNA-20a and showed less affinity toward SQSTM1. Hydrogen bonds and hydrophobic interactions were predicted. In contrast, lycopene showed less affinity toward miRNA-20a than resveratrol. Increasing doses of resveratrol, lycopene, and their combination induced a statistically significant reduction in mean percent viability and mean fold changes of miRNA-20a and SQSTM1 expression in treated HEp-2 cells. Pearson’s correlation showed a statistically significant positive correlation between miRNA-20a and SQSTM1 (R=0.812, p≤0.001). Grape and tomato extracts and their combination display promising cytotoxicity against HEp-2 cells in a dose- and time-dependent fashion. Both extracts reduce the expression of miRNA-20a and SQSTM1 with subsequent inhibition autophagy and promotion of apoptosis in HEp-2 cells.